Radiological evaluation of the normal patella position using the Insall-Salvati ratio - Ominde, Beryl Shitandi; Enaohwo, Mamerhi Taniyohwo; Erabocha, Onajite Gloria; Jeremiah, Ogheneyole; Ikubor, Joyce E; Omoro, Orovwoghene Faithful; Igbigbi, Patrick Sunday (Rzeszów University Press, 2025)
Introduction and aim. Normal patellofemoral relationship relies on the patella’s location which is vital in the knee’s stability and biomechanics. This research aimed to determine the normal Insall Salvati Ratio (ISR) and the cut-off values that will be useful for diagnosing patella alta and baja in Delta State in Nigeria. Material and methods. This retrospective cross-sectional study assessed the Insall-Salvati Ratio by dividing the patella tendon length by the patella length. These lengths were measured on lateral knee radiographs of 300 patients (149 males, 151 females) aged 20 years and older using digital calipers calibrated in cm. Results. With exception to the ISR, the measured variables showed sexual dimorphism and a significant weak negative association with age (p<0.05). Based on the international ISR cut-off values (<0.8 and >1.2), the prevalence of patella baja and alta was 15 (5%) and 64 (21.3%) respectively using the calculated cut-off values (<0.73 and >1.41). A lower prevalence of 6 (2%) and 9 (3%) were recorded correspondingly. Conclusion. The normal ISR cut-offs provided by this study will aid radiologists and orthopedic specialists in Delta State, Nigeria to precisely diagnose patella alta and baja and ensure proper restoration of the knee’s stability and biomechanics as well as minimizing complications.
This study due to its retrospective nature did not receive consent from subjects however ethical approval was sought from the Hospital’s research and ethics committee (DELSUTH/HREC/2024/004/0742). The study was carried out in compliance with the Declaration of Helsinki.
Keywords: alta; baja; height; insall-salvati ratio; length; patella